Phantom wormholes in Einstein-Maxwell-dilaton theory - Goulart, Prieslei [UNESP] (IOP Publishing, 2018)
In this paper we give an electrically charged traversable wormhole solution for the Einstein-Maxwell-dilaton theory when the dilaton is a phantom field, i.e. it has flipped sign kinetic term appearing in the action. In the limit when the charge is zero, we recover the anti-Fisher solution, which can be reduced to the Bronnikov-Ellis solution under certain choices of integration constants. The equations of motion of this theory share the same S-duality invariance of string theory, so the electrically charged solution is rotated into the magnetically charged one by applying such transformations. The scalar field is topological, so we compute its topological charge, and discuss that under appropriate boundary conditions we can have a lump, a kink, or an anti-kink profile. We determine the position of the throat, and show the embedding diagram of the wormhole. As a physical application, we apply the Gauss-Bonnet theorem to compute the deflection angle of a light-ray that passes close to the wormhole.
Keywords: exact solutions; Gauss-Bonnet theorem; wormholes